The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1111/j.1151-2916.2002.tb00475.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Activation of the Decomposition and Sintering of Kyanite

Abstract: The influence of attrition milling on the thermal decomposition of kyanite (Al2O3·SiO2) to mullite (3Al2O3·2SiO2) and SiO2, and its subsequent sintering, was studied. A commercial kyanite was attrition‐milled for times up to 12 h. Dilatometry confirmed that as‐received unmilled kyanite decomposes between 1300° and 1435°C. The decomposition reaction is slow initially and accelerates during the later stages until about one‐half of the decomposition occurs in the last 35°C. For the attrition‐milled kyanite, the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…Note that their morphology changes to a tabular one with rounded edges at elevated temperatures. This is consistent with microstructural descriptions from other studies [9]. The SEM images also revealed that sintered compacts produced from larger particle sizes result in larger pore sizes than those produced from smaller particle sizes, Table 4.…”
Section: Microstructuresupporting
confidence: 92%
“…Note that their morphology changes to a tabular one with rounded edges at elevated temperatures. This is consistent with microstructural descriptions from other studies [9]. The SEM images also revealed that sintered compacts produced from larger particle sizes result in larger pore sizes than those produced from smaller particle sizes, Table 4.…”
Section: Microstructuresupporting
confidence: 92%
“…In comparison, the main crystalline phases of the specimens with MoO 3 pretreated at 1150°C are α‐Al 2 O 3 , cristobalite (SiO 2 ), mullite, and traces of kyanite. Among these phases, cristobalite (SiO 2 ) and mullite are from the decomposition of kyanite (Kyanite (Al 2 O 3 ⊕SiO 2 ) decomposes into mullite (3Al 2 O 3 ⊕2SiO 2 ) and SiO 2 ) 17 . It was reported that the decomposition of kyanite and transformation to mullite took place between 1200 and 1400°C 18,19 .…”
Section: Resultsmentioning
confidence: 99%
“…2 When bauxite is heat treated at an elevated temperature, dehydration reaction takes place with gradual expulsion of water molecules through the intermediate formation of several metastable transition phases like chi (), eta (), gamma (), delta (), iota () theta (), kappa (), beta (), etc with progressive variation in crystallographic nature, specific surface area and grain morphology until the most stable form of alumina, corundum (-Al 2 O 3 ), is obtained. [3][4][5] Similarly, the dehydration-rehydration characteristics of cordierite-alumina composite precursor derived through semi-colloidal route have been reported to be very much dependent on dehydration temperature, relative humidity of the environment and alumina content of the composite precursor. 6 The present investigation deals with the careful study of dehydration-rehydration behaviour of gibbsitic bauxite rock of Indian origin with respect to variation of heat treatment temperature and relative humidity of the environment.…”
Section: Introductionmentioning
confidence: 99%